Coordination compounds of biogenic metals as cytotoxic agents in cancer therapy. (December 2021) - Guk, Dmitry A.; Krasnovskaya, Olga O.; Beloglazkina, Elena K.
Abstract: The review summarizes the data on the structures and methods for the synthesis of compounds with anticancer activity based on biogenic metals, which can replace platinum drugs prevailing in cytotoxic therapy. The main focus is given to the comparison of the mechanisms of the cytotoxic action of these complexes, their efficacy and prospects of their use in clinical practice. This is the first systematic review of cytotoxic zinc, iron, cobalt and copper compounds. The structure – activity relationships and the mechanisms of antitumour action are formulated for each type of metal complexes. The bibliography includes 181 references.